Unexpected release of phosphate and organic carbon to streams linked to declining nitrogen depositions. (30th September 2016) - Musolff, Andreas; Selle, Benny; Büttner, Olaf; Opitz, Michael; Tittel, Jörg
Abstract: Reductions in emissions have successfully led to a regional decline in atmospheric nitrogen depositions over the past 20 years. By analyzing long‐term data from 110 mountainous streams draining into German drinking water reservoirs, nitrate concentrations indeed declined in the majority of catchments. Furthermore, our meta‐analysis indicates that the declining nitrate levels are linked to the release of dissolved iron to streams likely due to a reductive dissolution of iron(III) minerals in riparian wetland soils. This dissolution process mobilized adsorbed compounds, such as phosphate, dissolved organic carbon and arsenic, resulting in concentration increases in the streams and higher inputs to receiving drinking water reservoirs. Reductive mobilization was most significant in catchments with stream nitrate concentrations <6 mg L −1 . Here, nitrate, as a competing electron acceptor, was too low in concentration to inhibit microbial iron(III) reduction. Consequently, observed trends were strongest in forested catchments, where nitrate concentrations were unaffected by agricultural and urban sources and which were therefore sensitive to reductions of atmospheric nitrogen depositions. We conclude that there is strong evidence that the decline in nitrogen deposition toward pre‐industrial conditions lowers the redox buffer in riparian soils, destabilizing formerly fixed problematic compounds, and results in serious implications for water quality.